Recreation activities to improve social behavior. Study in children and adolescents aged 9-14 - Calero Morales, Santiago; Fernández Lorenzo, Angie; Castillo de la Rosa, Francis Lenora (Revista Cubana de Medicina General Integral, 2016)
Introduction: Social conduct is a behaviour aimed at the society and among members of the same species, having influence in the surrounding environment, where ludic actions may play a role . Objective: The paper studies the effect of 15 recreational activities on the social behavior of children and adolescents in the Guamani neighborhood, south of the city of Quito, Republic of Ecuador. Method: Using a sample of 25 subjects with various problems of social behavior, aged 9-14 years, the research strategy starts with the diagnosis of 12 indicators or aspects of social life and manifestations of conduct. Results: The Friedman test determined the existence of significant differences between two (initial, p = 0.004, & final, p = 0.03) tests, with data obtained from the observation guides respectively, being the average ranks of the final tests, the best ones, demonstrating a significant difference between the initial and final test (p = 0.003) in the variable "Always" and the variable "Never" (p = 0.002) as determined by the Wilcoxon signed-rank test. Conclusion: The research shows that recreational activities are a viable and efficient alternative to improve social behavior in the sample studied.